Determination of heavy metals and other indicators in waters, soils and medicinal plants from Ave valley, in Portugal, and its correlation to urban and industrial pollution - Pinto, D. (2021)
The aim of this study was to evaluate pollution indicators on Rio Ave and surrounding environment, namely water, soil and medicinal plants in order to identify areas where contamination could cause ecosystem degradation. Plants, soil, surface water and ground water samples were collected seasonally at five different sampling sites along the Ave valley. Conductivity, pH, ammonium, nitrite and nitrate contents were evaluated. Cadmium, copper, lead, and zinc were measured in the water, soil and plants by Atomic Absorption Spectrophotometry. Results showed an increase on conductivity in waters from the origin to the mouth of the river. Nitrite levels were also higher than expected, especially in areas of wide industrialization and agricultural practices, where fertilizers widely used. Moreover, heavy metals in plants presented higher values when compared to those found in soils revealing that increased levels of heavy metals on soils are reflected similarly in plants. Levels of the analyzed parameters were often close or above to those legally acceptable in water and soils.